Community-acquired Legionnaires’ Disease in a Newly Constructed Apartment Building - Ryu, Sukhyun; Yang, Kyungho; Chun, Byung Chul (Journal of preventive medicine and public health, 2017)
Legionnaires' disease (LD) is a severe type of pneumonia caused by inhalation of aerosols contaminated with . On September 22, 2016, a single case of LD was reported from a newly built apartment building in Gyeonggi province. This article describes an epidemiologic investigation of LD and identification of the possible source of infection. To identify the source of LD, we interviewed the patient's husband using a questionnaire based on the management guidelines from the Korea Centers for Disease Control and Prevention. Water samples from the site were collected and analyzed. An epidemiological investigation of the residents and visitors in the apartment building was conducted for 14 days before the index patient's symptoms first appeared to 14 days after the implementation of environmental control measures. serogroup 1 was isolated from the heated-water samples from the patient's residence and the basement of the apartment complex. Thirty-two suspected cases were reported from the apartment building during the surveillance period, yet all were confirmed negative based on urinary antigen tests. The likely source of infection was the building's potable water, particularly heated water. Further study of effective monitoring systems in heated potable water should be considered.